Antimicrobial Suspectibility of Bacterial Isolated from Burn Unit in Dr. Hasan Sadikin General Hospital Bandung, Indonesia from June to September 2013 - Evila, Yodya; Sudigdoadi, Sunarjati; Soedjana, Hardisiswo (Althea Medical Journal, 2015)
Background: Development of infection in burned patients is a crucial matter because it may increase morbidity and mortality. Factors contributing to high risk for infections are disrupted skin barrier, dysfunction of the immune system and prolonged hospitalization. Crowded hospital condition and transfer of patients from one unit to another can affect development of infection caused by environmental factors. The aim of the study was to identify the antimicrobial suspectibility of bacterial isolated from Burn Unit in Dr. Hasan Sadikin General Hospital, Bandung.Methods: A descriptive study was carried out in Burn Unit Dr. Hasan Sadikin General Hospital Bandung, Indonesia, from June to September 2013.  A total of 30 environment samples were collected and cultured to identify the bacterias. Futhermore, the colonies  found, underwent antimicrobial susceptibility test.Results: Most common bacteria found from the environmental samples in Burn Unit was Staphylococcus saprophyticus (24%). Other bacterias found were Klebsiella pneumonia (17%), Acinetobacter baumanii (15%), Staphylococcus epidermidis (12%), Bacillus sp.(12%), Pseudomonas sp.(7%), Staphylococcus aureus (5%), Enterobacter aerogenes (5%) and Serratia sp. (2%). Some bacteria still had good sensitivity to antibiotics while the Enterobacteriaceae were almost completely resistant to antimicrobial used in the study.Conclusions: The most common bacteria found from the environment samples in Burn Unit is Staphylococcuss aprophyticus. Additionally, Klebsiella pneumoniae as one of the Enterobacteriaceae groups, appears as an emerging hospital associated infection pathogen with their resistant to many antimicrobials. DOI: 10.15850/amj.v2n3.592